REFORMULASI PENETAPAN LAHAN HIJAU DI KABUPATEN MALANG - Romdhoni, Romdhoni (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
This research results: First, there is a disharmony between the two rules in the determination of different numbers of green land, where the number contained in the LP2B regional regulation is 45,888.23 Ha, this figure is greater than the RTRW Perda which is 33,110, 3 Ha so there are the difference in green land area is 12,777.3 hectares. Generally in practice the green land is decreasing, not increasing. Second, the formation of the LP2B Perda is not participatory, this is proven because the Perda in its formation does not harmonize norms with the RTRW, whereas in the LP2B Law, it is mandated that the stipulation of LP2B must be adjusted to the RTRW. The impact of the norm uncertainty, first, has a negative impact on licensing factors in the investment sector. Thus the authors provide legal recommendations, which are reviewed first using the political political approach, which produces two main things that become the signs for changes in LP2B regional regulations, namely legal certainty in all fields and ideal community participation.Keywords: Reformulation, Perda LP2B and RTRW, Determination, and Green Land